2021
DOI: 10.1002/cctc.202001703
|View full text |Cite
|
Sign up to set email alerts
|

Impurity Control in Catalyst Design: The Role of Sodium in Promoting and Stabilizing Co and Co2C for Syngas Conversion

Abstract: The design of supported heterogeneous catalysts requires a detailed understanding of the structure and chemistry of the active surface. Although the chemical components of the active phase, support material, and process feed are typically considered to be the most important factors governing catalyst structure and performance, many common commercial supports contain trace impurities, which can have profound effects on catalyst properties. In this work, we study silica‐supported cobalt‐based catalysts, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Doping can be exploited to tailor the kinetics, selectivity, and stability of catalyst toward specific reactions. [39,40] As a platinum-group metal, Pd has similar electronic properties to Pt, but its stronger H absorption and adsorption behavior result in slow reaction rates in acidic-HOR. [10] Lattice distortions from the presence of B in bulk Pd [41] change its physical properties and B-doping modifies its catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Doping can be exploited to tailor the kinetics, selectivity, and stability of catalyst toward specific reactions. [39,40] As a platinum-group metal, Pd has similar electronic properties to Pt, but its stronger H absorption and adsorption behavior result in slow reaction rates in acidic-HOR. [10] Lattice distortions from the presence of B in bulk Pd [41] change its physical properties and B-doping modifies its catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggested that the added alkali metals may act as electron donors to cobalt, leading to stronger adsorption and enhanced dissociation of CO, which also benefits the formation of the Co 2 C phase. 47,50 The olefin/paraffin (O/P) ratio and the CO 2 selectivity also increased upon alkali addition. 6 Furthermore, the FTS reaction has been shown to be a structure-sensitive reaction, as different facets of Co 2 C were found to exhibit distinct catalytic activities toward CO dissociation, hydrogenation, and chain growth.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Atomic layer deposition (ALD) is an advanced thin film deposition technique that has gained wide interest for various technological applications in microelectronics, , catalysis, and renewable energy. ALD can be used to deposit a broad range of thin-film materials, including oxides, sulfides, and nitrides, as well as metals such as Ni, Cu, and noble metals. , ALD is a valuable vapor deposition technique due to its unique growth process wherein the precursors undergo alternating and self-limiting surface reactions. The layer-by-layer growth mechanism ideally leads to conformality and excellent control over the thickness.…”
Section: Introductionmentioning
confidence: 99%